Affordability of Canada's Food Guide: Current challenges amid COVID-19, War in Ukraine, and other world events - Taylor, Stacey; Charlebois, Sylvain; Music, Janet (Frontiers in Nutrition, 2023)
Since the 2019 Canada Food Guide was released there have been concerns raised over the cost of food, with an emphasis on the affordability of nutritious food. In this study, we evaluate the affordability of the 2019 Canada Food Guide in relation to the previous edition from 2007. As a result of the pandemic and other significant world events, many are feeling financial stresses as prices rise in many areas of life including housing, gas, and food. Our results show that it is more cost effective, on average, for children and teens to follow the 2019 Canada Food Guide, but more expensive for adults, when compared to the 2007 edition.